2020
DOI: 10.1371/journal.pone.0243725
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of HCC in chronic hepatitis C patients with pretreatment liver stiffness measurements below 17.5 kilopascal who achieve SVR following DAAs

Abstract: Background and aims To evaluate the ability of pretreatment liver stiffness measurements (pLSM) to predict hepatocellular carcinoma (HCC), incident decompensation and all-cause mortality in chronic hepatitis C (CHC) patients who achieved sustained virological response (SVR) after treatment with direct-acting antivirals (DAAs). Methods 773 CHC patients with SVR after DAA treatment and no prior liver complications were identified retrospectively. Optimized cut-off of 17.5 kPa for incident HCC was selected by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Recent reports indicate that HCV patients may also die from liver-related complications even after SVR[ 154 , 177 ]. Likewise, all-cause mortality is still high after SVR in cirrhotic patients[ 178 ]. SVR after IFN-based treatment offered no survival benefit after 10 years of follow-up even in the specific group of hemophiliacs[ 142 ].…”
Section: What Svr Really Representsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports indicate that HCV patients may also die from liver-related complications even after SVR[ 154 , 177 ]. Likewise, all-cause mortality is still high after SVR in cirrhotic patients[ 178 ]. SVR after IFN-based treatment offered no survival benefit after 10 years of follow-up even in the specific group of hemophiliacs[ 142 ].…”
Section: What Svr Really Representsmentioning
confidence: 99%
“…Maintenance of glycated hemoglobin level below 7.0% reduced the development of HCC[ 292 ]. Diabetes was independently associated with both de novo HCC occurrence and HCC recurrence after DAA treatment[ 178 , 293 ]. A systematic review of seven cohort and two case-control studies has confirmed the significant contribution of T2DM in the development of HCC in HCV-infected patients[ 278 ].…”
Section: Hcv and Metabolic Syndromementioning
confidence: 99%
“…Baseline LSM obtained by Acoustic Radiation Force Impulse (ARFI) or TE, was associated with an increased risk of post-treatment HCC ( Table 5 ) in three studies analysing SVR patients. 53 , 56 , 57 Tachi et al identified the 1.73 m/s threshold as the optimal cut-off to stratify CHC patients according to their de-novo HCC risk 56 ( Table 5 ). In the other two studies, baseline LSM ≥20 kPa and ≥17.5 kPa were associated with HCC occurrence in 398 and 773 CHC patients from Japan and Denmark, respectively.…”
Section: Predictors Of De-novo Hccmentioning
confidence: 99%
“…In both studies, the prevalence of cirrhosis was not reported. 53 , 57 Ogasawara et al reported that also SVR24-LSM (ie, LSM performed 24 weeks after EOT) ≥10 kPa was independently associated with de-novo HCC. 57 This finding was in line with two other Japanese studies, identifying in LSM ≥3.75 kPa obtained through Magnetic Resonance Elastography (MRE) 12 weeks after treatment completion (SVR12-MRE) an independent predictor of HCC occurrence.…”
Section: Predictors Of De-novo Hccmentioning
confidence: 99%
See 1 more Smart Citation